Pengaruh Beby Tsabina sebagai Brand Ambassador dan Harga terhadap Keputusan Pembelian Barenbliss - Surianto Surianto; Marsella Valentina (Jurnal Syntax Admiration, 2024)
The purpose of this study is to calculate the impact of Barenbliss brand ambassadors on consumer propensity to buy products, identify how price affects consumer choices in buying Barenbliss products, and find out how much price and Beby Tsabina as brand ambassadors influence people's choices to buy Barenbliss products. This research method uses a survey approach developed through the use of questionnaires prepared based on literature and statement items. The results were, first, that the brand ambassador (X1) had a positive impact on the purchase decision (Y) on the Barenbliss brand, so the first hypothesis was accepted; second, the price (X2) also has a positive impact on the purchase decision (Y) on the Barenbliss brand, so the second hypothesis is accepted; and third, simultaneously, brand ambassador (X1) and price (X2) positively impact the purchase decision (Y) on the Barenbliss brand, so the third hypothesis is accepted.